Analysis of changes in the chemokine CXC ligand 13 in serum and cerebrospinal fluid of patients with neuromyelitis optica - Juan Zhou; Shalin Luo; Xiaoxi Yao; Haipeng Li; Ying Wen (Scientific Reports)
Abstract To determine correlation between the Extended Disability Status Scale(EDSS) grade and the progression of neuromyelitis optica(NMO) patients’ levels of the chemokine CXC ligand 13 (CXCL13) in their serum and cerebrospinal fluid. This research included forty-one patients diagnosed with neuromyelitis optica(NMO) and forty-three patients diagnosed with multiple sclerosis(MS). The control group consisted of forty-three non-inflammatory neurological disease(NND) patients. The patients’ serum and cerebrospinal fluid CXCL13 levels were measured. Patients in NMO group and MS group had serum and cerebrospinal fluid with CXCL13 levels that were substantially greater than those in the NND group. When comparing the CXCL13 levels of blood and cerebrospinal fluid between patients in the EDSS ≥ 3.5 group and the EDSS<3.5 group, with the EDSS ≥ 3.5 group’s CXCL13 levels being greater(P<0.05). There was a positive correlation between the serum CXCL13 and the EDSS grades of both the NMO and MS groups(r = 0.884, P < 0.001); The cerebrospinal fluid CXCL13 of the NMO and MS groups showed a positive correlation with their EDSS grades(r = 0.681, P < 0.001). EDSS scores of NMO patients were positively correlated with their serum BLC-1 (r = 0.896, P < 0.001); EDSS scores of NMO patients were positively correlated with their cerebrospinal fluid BLC-1 (r = 0.678, P < 0.001).EDSS scores of MS patients were positively correlated with their serum BLC-1 (r = 0.852, P < 0.001); EDSS scores of MS patients were positively correlated with their cerebrospinal fluid BLC-1 (r = 0.613, P < 0.001). Serum and cerebrospinal fluid levels of CXCL13 may serve as an important biomarker for the presumptive assessment of the degree of disability in NMO and MS disease, providing a basis for the treatment and control of the disease.